Study guides

☆☆

Q: X2 plus 6X plus 5 equals 0?

Write your answer...

Submit

Still have questions?

Related questions

x2 + 6x + 9 = 81 x2 + 6x = 72 x2 + 6x - 72 = 0 (x+12)(x-6) = 0 x= -12, 6 (two solutions)

x2 + 6x + 12 = 0 x2 + 6x + 9 = -3 (x + 3)2 = -3 x + 3 = ± √-3 x = -3 ± i√3

x2+6x-40 = 0 (x+10)(x-4) = 0 x = 4 or x = -10

A quadratic equation. If you wish to solve for x, you can do so as follows: -x2 + 6x + 7 = 0 x2 - 6x - 7 = 0 (x - 7)(x + 1) = 0 x ∈ {-1, 7}

x2 + 6x - 2 = 0 x2 + 6x + 9 = 13 (x + 3)2 = 13 x + 3 = ± √13 x = -3 ± √13

x2 + 6x + 8 = 0 Solve for x.X = -2 or X = -4

x2 + 6x - 110 = 0 ∴ x2 + 6x = 110 ∴ x2 + 6x + 36 = 146 ∴ (x + 6)2 = 146 ∴ x + 6 = ±1461/2 ∴ x = -6 ±1461/2 ∴ x ≈ 6.083, 18.083

(x - 3)(x - 2)

x2 + 6x = 16=> x2 + 6x - 16 = 0=> x2 + 8x -2x - 16 = 0=> (x+8)(x-2) = 0=> x = -8 or x = 2So, the solutions of the quadratic equation x2 + 6x = 16 are -8 and 2.

x2+6x+9 = x+3 x2+6x-x+9-3 = 0 x2+5x+6 = 0 Solve by factoring or with the help of the quadratic equation formula: (x+3)(x+2) = 0 Therefore: x = -3 or x = -2

No answer in integers. Quadratic formula gives roots as -1.268 and -4.732

x2 +6x = 27 x2 + 6x - 27 = 0 x2 + 9x - 3x - 27 = 0 x(x + 9) - 3(x + 9) =0 (x - 3)(x + 9) = 0 So x can equal 3 or -9.

(x + 12)(x - 6) = 0 x = 6 or -12

x^2 + 3x + 7 = 6x + 18 x^2 - 3x - 11 = 0

x2 + 6x + 1 = 0 x2 + 6x + 9 = 8 (x + 3)2 = 8 x + 3 = ± 2√2 x + 3 = -3 ± 2√2 x ∈ {-3 - 2√2, -3 + 2√2}

x = 2 and x = 4

hyperbola

If: x2-6x-13 = 14 Then: x2-6x-27 = 0 And: (x+3)(x-9) = 0 So: x = -3 or x = 9

Factors are (x + 5)(x + 1) so x = -5 or -1

(x-5)(x-6) so x=5,6

x^2+6x+2=9 x^2+6x-7=0 (x+7)(x-1)=0 x=-6,1 for your roots

x-intercept happens when y=0 0=x2+6x-7 0=(x - 1)(x + 7) x-intercepts are x=1 and -7

x²+6x+9=49 x²+6x-40=0 x1=-6/2 - Square root of ((6/2)²+40) x1=-3 - 7 x1= -10 x2=-6/2 + Square root of ((6/2)²+40) x2=-3 + 7 x2= 4

5x2-2x+16=4x2+6x ,or x2-8x+16=0, or x2-2(x)(4)+(4)2=0, or (x-4)2=0, or (x-4)(x-4)=0, or x=4

x2 - 6x + 8 = 0 x2 - 4x - 2x + 8 = 0 x*(x - 4) - 2*(x - 4) = 0 (x - 2)*(x - 4) = 0 so (x - 2) = 0 or (x - 4) = 0 ie x = 2 or x = 4